Specificity of insulin signalling in human skeletal muscle as revealed by small interfering RNA - Krook, A; Zierath, J. R (Diabetologia, 2009)
Insulin action on metabolically active tissues is a complex process involving positive and negative feedback regulation to control whole body glucose homeostasis. At the cellular level, glucose and lipid metabolism, as well as protein synthesis, are controlled through canonical insulin signalling cascades. The discovery of small interfering RNA (siRNA) allows for the molecular dissection of critical components of the regulation of metabolic and gene regulatory events in insulin-sensitive tissues. The application of siRNA to tissues of human origin allows for the molecular dissection of the mechanism(s) regulating glucose and lipid metabolism. Penetration of the pathways controlling insulin action in human tissue may aid in discovery efforts to develop diabetes prevention and treatment strategies. This review will focus on the use of siRNA to validate critical regulators controlling insulin action in human skeletal muscle, a key organ important for the control of whole body insulin-mediated glucose uptake and metabolism.